2009
DOI: 10.1253/circj.cj-09-0392
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dilation Responses of Rat Small Mesenteric Arteries at High Intravascular Pressure in Spontaneously Hypertensive Rats

Abstract: ypertension is a multifactorial, polygenic disease and is an important risk factor for the development of atherosclerosis and cardiovascular diseases. [1][2][3][4] It is well established that chronic hypertension is associated with the structural and functional changes in the resistance vasculature that are responsible for the elevated peripheral resistance in hypertension; 1,5,6 such structural alterations are termed "vascular remodeling". In the majority of hypertension models studied, the internal diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The effects of increased intraluminal pressure and transient hypertension on microvascular function have been studied in both animal models 9-11 and in isolated human arterioles, 7 but this is the first study, to our knowledge, to demonstrate a differential response to a pressure stimulus in the microvasculature of exercise trained and sedentary adults. Because weight lifting causes transient increases in blood pressure, it could be hypothesized that this repeated exposure to elevated blood pressures has a conditioning effect on the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of increased intraluminal pressure and transient hypertension on microvascular function have been studied in both animal models 9-11 and in isolated human arterioles, 7 but this is the first study, to our knowledge, to demonstrate a differential response to a pressure stimulus in the microvasculature of exercise trained and sedentary adults. Because weight lifting causes transient increases in blood pressure, it could be hypothesized that this repeated exposure to elevated blood pressures has a conditioning effect on the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Gündüz and colleagues demonstrated normal ACh- and flow-mediated dilation in mesenteric arteries of spontaneously hypertensive rats after the arteries were exposed to high intraluminal pressure; whereas arteries from normotensive Wistar Kyoto rats showed blunted dilation to both stimulus after exposure to the same high pressure insult. 11 …”
Section: Discussionmentioning
confidence: 99%
“…In humans, counter-regulatory vasodilatory events have also been tested using endothelium-independent agents, such as sodium nitroprusside (SNP), and were not different between control and hypertensive subjects 149,151 . Conversely, endothelial-dependent vasodilation by acetylcholine was impaired in hypertensive patients and animal models, but the amount of experimental variability in these observations may be a red-herring in interpreting the outcome of studies of VSMC function in hypertension 149,152,153 . Nonetheless, it remains critically important to test the complex signaling pathways used to balance vasoconstriction and counteracting vasodilatory forces, which, under pathological conditions cause hyperconstriction, increased vascular resistance, and high blood pressure.…”
Section: Resistance Artery Remodelingmentioning
confidence: 99%
“…Previous in vitro studies conducted in pressurized small arteries including MSAs have shown that endothelium-dependent vasodilation [2,3,4,5,9,10] evoked by flow- and receptor-selective agonists is significantly reduced with increases of TMP. Endothelium-independent vasodilation induced by the NO donors, SNP or SNAP, were also reduced by TMP elevation [2,3,4,9]. However, in the present study, the lack of acute pressure effects on BK as well as NO donor-evoked vasodilation suggests that in PGF2α-preconstricted MSVs the activity of endothelial NOS and VSM guanylyl cyclase is not altered.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelium-dependent vasodilation has been widely investigated in the arteries with some studies showing the presence of endothelium dysfunction in mesenteric small arteries (MSAs) of healthy rats studied in vitro at a high level of transmural pressure (TMP) [2,3]. An impaired endothelial dilator function has also been reported in some disease conditions in arteries [4,5,6,7,8], including studies in rat mesentery [9,10]. The findings of these studies suggest that high levels of TMP may be harmful to the vascular regulatory function of the endothelium mainly via reducing NO function, which has been considered as a major pathogenesis of hypertension.…”
Section: Introductionmentioning
confidence: 99%